PERAN POSBAKUM DI PENGADILAN AGAMA METRO MASA NEW NORMAL - Fimansyah; Nyimas Lidya Putri Pertiwi (LPPM STAI DARUSSALAM LAMPUNG, 2021)
This article aims to describe the efforts of Posbakum in providing services at the Metro Religious Courts during the new normal period. Posbakum is an institution that provides legal assistance services for people seeking justice who are economically unable to pay for advocate services facilitated by the state in every Religious Court/Shari'ah Court. During the Covid-19 pandemic, Posbakum continued to provide services online or offline by implementing health protocols, namely: Implementing physical distancing, Requiring wearing masks, Encouraging to wash hands, Installing transparent hijabs, Restricting service hours. So that the judicial process and services to the justice-seeking community can still run according to procedure.